Pre-loved luxury: identifying the meaning of second hand luxury possessions. Issue 1 (16th March 2015) - Turunen, Linda Lisa Maria; Leipämaa-Leskinen, Hanna
Abstract : Purpose: – The purpose of this study is to shed light on the consumption of second-hand luxury brands, identifying the meanings attached to second-hand luxury possessions in the context of fashion and, specifically, in the case of luxury accessories. Prior discussions of luxury consumption and marketing have focused on brand-new luxury goods, thus largely neglecting the emergence of markets for used luxury products. Design/methodology/approach: – The empirical data for this study were generated through interviews with ten Finnish women and through fashion blogs concerning luxury goods that are bought second-hand. Findings: – The findings show that second-hand luxury possessions are characterized by five different meaning themes: Sustainable Choice, Real Deal, Pre-loved Treasure, Risk Investment and Unique Find. The study highlights how consumers are able to achieve luxury experiences even without exclusive service, as the informants attached meanings of luxury to second-hand luxury possessions, especially with regard to the symbolic value and authenticity of the product. However, the meaning of authenticity appears to be a double-edged sword in this context, as consumers may also consider that they are taking a financial as well as reputational risk when acquiring a previously owned luxury item. Originality/value: – This study brings forward novel viewpoints to discussions on luxury brand marketing by connecting the issue with the topical phenomenon of second-hand and luxury consumption. The study suggests important managerial implications for luxury brand marketers.